Elements of Egalitarianism in Ellenistica Utopias Theopompus, Iambulusus and Euhemerus: from Greek Classics to the Stoic Idea of "ΚΟΙΝΟΣ ΒΙΟΣ" - Khazina, Anna; Safronova, Lidiya; Sivkina, Natalia; Chougounova, Tatiana; Chepurnowa, Natalya ,; Shlyakhov, Mikhail; Nochtvina, Bella (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the social models of Hellenistic utopias from the point of view of specific values of the means of the simulated societies. The analysis of utopian writings by Theopompus, Iambulusus, Euhemerus, united in the "Historical library" by Diodorus Siculus, allows to highlight their common paradigm which is the justification of the priority of "common life", which is based on egalitarianism concerning ownership, distribution, family, lifestyle. The sense of the egalitarian elements that determine the specificity of the utopian field of the investigated projects is restored in the context of classical ancient concepts of the origin of human society and social institutions, as well as in the context of Hellenistic stoic ideas about the "common life".